2014
DOI: 10.1111/jdv.12702
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized exploratory study comparing the efficacy of once‐daily topical 0.5% 5‐fluorouracil in combination with 10.0% salicylic acid (5‐FU/SA) vs. cryosurgery for the treatment of hyperkeratotic actinic keratosis

Abstract: A prospective randomized exploratory study comparing the efficacy of once-daily topical 0.5% 5-fluorouracil in combination with 10.0% salicylic acid (5-FU/SA) vs. cryosurgery for the treatment of hyperkeratotic actinic keratosis Mean change in lesion count from baseline to Day 98 was À5.2 and À5.7 lesions per patient for 0.5% 5-FU/SA and cryotherapy groups respectively. Histological AK clearance rates on Day 98 were 62.1% and 41.9% respectively. At 6-month posttreatment follow-up, recurrence of cleared lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 31 publications
0
43
0
2
Order By: Relevance
“…The aim of this study was to evaluate in vivo the changes in skin affected with AK and subclinical AK using different imaging technologies and the effect of treatment with 0.5% 5‐fluorouracil and 10% salicylic acid on the lesions. Recent studies have confirmed the efficacy of this drug and cost‐effectiveness in the treatment of AKs . Recently, Ulrich et al .…”
Section: Discussionmentioning
confidence: 87%
“…The aim of this study was to evaluate in vivo the changes in skin affected with AK and subclinical AK using different imaging technologies and the effect of treatment with 0.5% 5‐fluorouracil and 10% salicylic acid on the lesions. Recent studies have confirmed the efficacy of this drug and cost‐effectiveness in the treatment of AKs . Recently, Ulrich et al .…”
Section: Discussionmentioning
confidence: 87%
“…Cryosurgery has been the treatment of choice for focal lesions, and the British Association of Dermatologists suggests that it could be used for hypertrophic lesions (Bourke, Coulson, & English, ). One research group (Simon et al, ) compared 5‐FU/SA and cryosurgery as AK treatments. At the 6‐month post‐treatment follow‐up, total clearance of the lesions was observed in 60.6% of the patients in the 0.5% 5‐FU/SA group and 15.2% of the patients in the cryosurgery group.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed more than a half (51.2%) of pro III graded AKs had adnexal involvement. This may have an impact on the choice of treatment as many lesion directed treatments target superficial disease and are not effective when there is deep follicular involvement, increasing the risk of recurrence …”
Section: Discussionmentioning
confidence: 99%